Physical and thermal properties of l-lactide/ϵ-caprolactone copolymers: the role of microstructural design - Sawarot Phetsuk (2020)
© 2019 Society of Chemical Industry Understanding the underlying role of microstructural design in polymers allows for the manipulation and control of properties for a wide range of specific applications. As such, this work focuses on the study of microstructure–property relationships in l-lactide/ϵ-caprolactone (LL/CL) copolymers. One-step and two-step bulk ring-opening polymerization (ROP) procedures were employed to synthesize LL/CL copolymers of various compositions and chain microstructures. In the one-step procedure, LL and CL were simultaneously copolymerized to yield P(LL-stat-CL) statistical copolymers. In the two-step procedure, poly(l-lactide) (PLL) and poly(ϵ-caprolactone) (PCL) prepolymers were synthesized in the first step before CL and LL respectively were added in the second step to yield P[LL-b-(CL-stat-LL)-b-LL] and P[CL-b-(LL-stat-CL)-b-CL] block copolymers as the final products. The findings reveal that, in addition to the copolymerization procedure employed, the length and type of the prepolymer play important roles in determining the chain microstructure and thereby the overall properties of the final copolymer. Moreover, control over the degree of crystallinity and the type of crystalline domains, which is controlled during the polymer chemistry process, heavily influences the physical and mechanical properties of the final polymer. In summary, this work describes an interesting approach to the microstructural design of biodegradable copolymers of LL and CL for potential use in biomedical applications. © 2019 Society of Chemical Industry.